2003
DOI: 10.1074/jbc.m204783200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Apaf-1/Caspase-9 Apoptosome by Caspase-3 and XIAP

Abstract: The apoptosome is a multiprotein complex comprising Apaf-1, cytochrome c, and caspase-9 that functions to activate caspase-3 downstream of mitochondria in response to apoptotic signals. Binding of cytochrome c and dATP to Apaf-1 in the cytosol leads to the assembly of a heptameric complex in which each Apaf-1 subunit is bound noncovalently to a procaspase-9 subunit via their respective CARD domains. Assembly of the apoptosome results in the proteolytic cleavage of procaspase-9 at the cleavage site PEPD 315 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(159 citation statements)
references
References 29 publications
6
152
1
Order By: Relevance
“…5). The association of the cytosolic cytochrome c along with Apaf-1 and pro-caspase-9 contributes to the formation of apoptosome leading to activation of caspase-9 [45], which then activates effector caspases such as caspase-3 [46]. We found that apoptosis occurred in all three glioblastoma cell lines with activation of caspase-9 as well as of caspase-3 for apoptosis, which in turn caused ICAD fragmentation (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…5). The association of the cytosolic cytochrome c along with Apaf-1 and pro-caspase-9 contributes to the formation of apoptosome leading to activation of caspase-9 [45], which then activates effector caspases such as caspase-3 [46]. We found that apoptosis occurred in all three glioblastoma cell lines with activation of caspase-9 as well as of caspase-3 for apoptosis, which in turn caused ICAD fragmentation (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…This proteolytic event further increases the enzymatic activity of caspase-9, and was proposed to remove the peptide sequence that binds XIAP . However, recent work suggests that XIAP BIR3 can still interact with and inhibit the enzyme activity of processed caspase-9 in the apoptosome complex (Zou et al, 2003).…”
Section: Iap Bir Domains Bind and Inhibit Caspasesmentioning
confidence: 99%
“…In this case, removal of XIAP allows for complete caspase-3 maturation through an autocatalytic process. Caspase-3 then cleaves caspase-9 at an alternative site leading to the generation of the p37 fragment seen in the western blot ( Figure 4d; Zou et al, 2003). Autoprocessing of caspase-9 then generates the p35 fragment.…”
Section: Trail-resistance In Sw620 Cells Is Downstream Of Bid Cleavagementioning
confidence: 99%